PENJUALAN TERHADAP KEPUASAN KONSUMEN PT. INDOFOOD SUKSES MAKMUR. Tbk BOGASARI FLOUR MILLS DI JAKARTA - Wahyu Murti dan Oman Pardepi (Jurnal Manajemen FE-UB, 2015)
The purpose of this study is to analyze the effect of simultaneous and partial product quality, service quality and Sales Promotion of consumer satisfaction PT. Indofood Sukses Makmur Tbk. Bogasari Flour Mills in Jakarta.The variables that theoretically influence the relationship between the independent variables to the Dependent variable are the interverning variables in this case, as the observed variable and able to directly correlate between the Independent variables (Product Quality, Service Quality and Sales Promotion) to the Dependent variable (Customer Satisfaction). By taking samples of 80 consumers of PT. Indofood Sukses Makmur Tbk. Bogasari Flour Mills in Jakarta.To solve the problem by analyzing and testing the relationship and influence between independent variables on dependent variable used by causalistic model through path analysis (Path Analisys) with SPSS 20.2. Keywords: Product Quality, Service Quality, Sales Promotion and Consumer Satisfaction.